Cohort Profile: the Etude Epidémiologique sur les Petits Ages Gestationnels-2 (EPIPAGE-2) preterm birth cohort - Lorthe, E (2021)
Medical practices and the organization of care vary widely across countries and have markedly evolved over the past two decades. The prognosis of very preterm infants has changed accordingly, raising new questions and requiring new assessments. We therefore set up the EPIPAGE-2 cohort, a new longitudinal study of preterm infants, with the following objectives: to provide actualized estimates of short- and long-term outcomes for extremely, very and moderately preterm babies and their families; to study changes in practices at both individual and organizational levels and their impact on child health and development; and to explore aetiologies of preterm birth and identify early predictors of adverse outcomes.